Photodissociation of water molecule at short photon wavelengths: Dynamical studies - Peng, Yigeng; Hu, Xiaoqing; Wu, Yong; Wang, Jianguo; Lu, Ruifeng; Sisourat, Nicolas (Frontiers in Physics, 2023)
In our last study [J. Phys. B At. Mol. Opt. Phys. 54, 125102 (2021).], we reported the ab-initio calculation of the full-dimensional potential energy surfaces of water molecule including 9 A’ and 9 A” states in Cs symmetry. In this study, we performed additional non-adiabatic semi-classical studies based on the potential energy surfaces. Our simulation successfully repeated the near picosecond lifetime of the F ̃(_^1)A' state measured by time resolved photo-electron spectra experiment [Chinese J. Chem. Phys. 32, 53 (2019)]. We also determined the dissociation branching ratio including H+OH(X, A), H+H+O and H2+O channels. In addition, the reaction path corresponding to H2+O(1S) channel is clearly marked out, which is found in recent free-electron laser experiment [Nat. Commun. 12, 6303 (2021)].